Dinamika Lingkungan dan Psikologi dalam Pembentukan Perilaku Sosioapatik - Amanda Hanifah; Jeneri Arbinto Toraja; Lira Firna Panggabean; Putri Ramadhani Lubis; Sisilia Brigita Siahaan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the dynamics of the environment and psychological factors in the formation of sociopathic behavior in individuals. Sociopathic behavior, often characterized by an inability to empathize and a disregard for social norms, is influenced by various interrelated factors, both external and psychological. The study uses a descriptive approach with a qualitative method to understand how external factors such as family dynamics, social environment, as well as internal factors such as psychological disorders and personality traits, contribute to the development of antisocial behavior. The results indicate that the interaction between negative environmental pressures, such as family violence, and psychological disorders like antisocial personality disorder, exacerbates sociopathic behavior. Furthermore, psychological factors such as lack of self-control and difficulties in building interpersonal relationships also play a significant role in the development of such behavior. This study suggests the importance of early intervention and a comprehensive approach in addressing individuals showing signs of sociopathic tendencies, particularly those related to psychological conditions and deep environmental influences.